2.7k views
1 vote
Give the function f(x) = 3 ^ x - 4x determine the average rate of change from x = 1 x = 2

User Shmiddty
by
5.7k points

1 Answer

5 votes

Answer:

2

Explanation:

Given the average rate of change formula, we must first find the x and y values of the function.

We are provided with the two x values, 1 and 2. We now need to find the output, or y.

ƒ(x)=3^x-4x

ƒ(1)=3-4=-1

ƒ(2)=9-8=1

Then, we use the formula (ƒ(2)-ƒ(1))/x2-x1(subscripts here, in case you multiplied) which gets us 2/1, or 2. Therefore, the average rate of change(ARC) is 2. I believe you just need to find the output and subtract if they are exactly one whole number apart, but don't quote me on that.

User Santanu Bera
by
5.9k points